Political Interest Reflected In Orhan Pamuk's Istanbul Memoir (2003): A Sociological Approach - Hamitayani, Mutik, Dr. Phil. Dewi Candraningrum, M.Ed, Drs. Abdillah Nugroho, M. Hum (2015)
The major problem of this study is how the importance of social skill is reflected in Istanbul memoir by Orhan Pamuk. The objective of this study is to analyze the memoir based on its structural elements and to describe the importance of social skill in the memoir based on the sociological analysis. In analyzing Istanbul, the researcher uses qualitative method and sociological approach. The data sources consist of primary data and secondary data sources. The primary data source is Istanbul memoir and the secondary data sources are the other sources related to the analysis such as books of literary theory and the other relevant information. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, the memoir describes the social condition in Turkey that there are many differences between the western culture and the east culture. Second, Orhan Pamuk criticizes the real life condition in Turkey because the social life in Turkey was slumped because of the political history cause raged society and communities affected. The ends of the memoir is by making the major character, Orhan Pamuk wants to change the condition in Turkey.